Healthy workplace with ergonomics among software engineers: a review - Maruthappapandian, Jasmine; Chellaiyan, Vinoth Gnana; Ali, Fasna Liaquath; Avinash, Deepak (International Journal Of Community Medicine And Public Health, 2019)
Estimate on the prevalence of musculoskeletal problems among the software engineers vary widely across globe. The main cause of this work-related musculoskeletal problem is due to improper usage of ergonomics. The objective of this review is to discuss the role or principles of ergonomics on preventing musculoskeletal problem among software engineers. Multiple databases (PubMed, Medline, Embase and Google Scholar) were searched for studies on the prevalence of musculoskeletal problem among software engineers and the implications of ergonomic interventions on these problems. The studies were prioritized according to validity and quality. Only a few studies were done to identify the knowledge or awareness about the ergonomic positions, practise of the ergonomic principles, its association with the prevalence of musculoskeletal problems, do the organisation provides regular ergonomic check of the workstation, do the software professionals have a regular health check-up.